Some Vocational Counselling Construct Underpinnings Within the "Choice" System - Turgeon, Pierre-Paul (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of the presentation is to develop some of the vocational construct underpinnings within the "CHOICES" system. CHOICES, the author feels, could help make it possible for counsellors to prepare clients to explore an extensive computerized data file and to examine ways in which their personal criteria for selecting occupations, educational and training programs, influenced the range of opportunities available to them. By making choices immediately through reality testing in a low risk counselling environment the counsellor and client are provided with valuable data within a vocational counselling experience.